Zew nihilizmu, czyli o relatywności prawdy hermeneutycznej - Kalaga, Tomasz (Er(r)go. Teoria - Literatura - Kultura, 2005)
Tomasz Kalaga's review of Beyond Interpetation. The Meaning of Hermeneutics for Philosophy" by Gianni Vattimo (1997).